Multiple Normative Expectations and Interventions -Experimental Evidence on Whistleblowing Behaviour - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina
Normative expectations – beliefs about what others perceive as appropriate – have been shown to influence behavioural choices across various domains. We examine this concept in the context of whistleblowing, where potential whistleblowers face two competing norms: promoting fairness by reporting wrongdoing versus maintaining loyalty to peers by staying silent. We investigate how normative expectations about these two mutually exclusive actions affect reporting decisions. Specifically, we test whether providing information on the majority beliefs about either the appropriateness of whistleblowing, or of staying silent, or about both behaviours together, differentially affects the whistleblowing decision. Using an incentivized experiment with UK employees on Prolific, our study yields four key findings: First, employees are more likely to report misconduct when they believe that the majority considers whistleblowing to be appropriate. Second, they are less likely to blow the whistle when they believe staying silent is deemed appropriate. Third, this effect prevails for a particularly important subgroup: among employees who believe that the majority supports whistleblowing, the reporting probability increases substantially when they simultaneously expect that staying silent is deemed inappropriate. Fourth, providing information about both normative dimensions combined or only about the inappropriateness of staying silent significantly increases whistleblowing compared to the (no information) baseline and to information about whistleblowing appropriateness alone. These findings demonstrate the importance of normative expectations about both behavioural options for accurately predicting whistleblowing behaviour, and that social information interventions are most effective when they target behaviours where appropriateness beliefs about conflicting options are dispersed.
Keywords: Whistleblowing; Normative Expectations; Social Information Intervention; Social Norms; Economic Experiment

“I don’t believe that you believe what I believe”: an experiment on misperceptions of social norms and whistleblowing - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina
Social norms fundamentally shape economic decision-making, yet individuals often systematically misperceive what others think and do, potentially leading to suboptimal social outcomes. We examine how such misperceptions affect behaviour and whether correcting them can induce a behavioural change, using whistleblowing as an application. Through survey data and an incentivized laboratory experiment, we demonstrate that while a majority of individuals (>75%) privately support whistleblowing, almost half (45.92%) misperceive the majority’s view. Both personal normative beliefs and normative expectations strongly predict whistleblowing behaviour. Their alignment is particularly noteworthy: individuals who personally support whistleblowing are more likely to report misconduct when they believe others share their views. A social information intervention revealing the true distribution of peer support affects subgroups differently: while it increases whistleblowing behaviour among individuals who already personally favour reporting misconduct, there is no effect among those who are personally resistant to it. Still, given the relatively low cost of such social information interventions, they offer an economically viable means of achieving behavioural change in at least some of the targeted individuals.
Keywords: Social Norms; Normative Expectations; Personal Normative Belief; Misperceptions; Whistleblowing